Characterizing the relationships between patient‐reported outcomes and clinician assessments of alopecia areata in a phase 2a randomized trial of ritlecitinib and brepocitinib. (25th January 2022) - Winnette, R.; Banerjee, A.; Sikirica, V.; Peeva, E.; Wyrwich, K.
Abstract: Background: The phase 2a ALLEGRO trial (NCT02974868) investigated the safety and efficacy of ritlecitinib (PF‐06651600) and brepocitinib (PF‐06700841) in adults with alopecia areata. No randomized controlled trial for alopecia areata has evaluated correlations between clinician‐assessed hair loss and patient‐reported outcomes. Objectives: Report scores from the Alopecia Areata Symptom Impact Scale (AASIS; a patient‐reported outcome tool) and explore the relationships of those scores with clinician‐assessed Severity of Alopecia Tool (SALT) scores at baseline and week 24 of the ALLEGRO trial. Methods: Adults with alopecia areata were randomized to ritlecitinib ( n = 48), brepocitinib ( n = 47) or placebo ( n = 47). After 24 weeks, the mixed‐effects model with repeated measures was used to calculate the active treatment groups' AASIS score least‐squares mean differences. Relationships between AASIS and SALT scores at baseline and week 24 were evaluated by Pearson's correlation coefficients using pooled data. Results: Baseline AASIS and SALT scores were similar among treatment groups. Both active treatment groups reported significant improvements in AASIS scores at week 24 (least‐squares mean differences vs. placebo for ritlecitinib, −0.8 to −2.3; brepocitinib, −0.9 to −3.7; P < 0.05 for all). At week 24, the mean SALT scores (standard deviation) improved compared with baseline [ritlecitinib, 54.4 (40.3) vs. 89.4 (15.8); brepocitinib, 31.9 (35.7) vs. 86.4 (18.1)]. The correlation coefficients between AASIS global and subscale scores and SALT scores at week 24 ranged from 0.34 to 0.58; P < 0.05 for all. Conclusions: Patients randomized to ritlecitinib or brepocitinib reported significantly improved AASIS and SALT scores at week 24 of the ALLEGRO trial compared to placebo. At week 24, medium‐to‐large correlations can be seen between AASIS global and subscale scores and SALT scores. Our experience with AASIS instrument highlighted several aspects that suggest new patient‐reported outcome tools are needed to accurately assess patients' relevant alopecia areata related signs, symptoms and daily functioning. Abstract : Linked Commentary: H.A. Ramírez‐Marín & A. Tosti J Eur Acad Dermatol Venereol 2022; 36 : 494–495. https://doi.org/10.1111/jdv.17984 .